Assessment of the analytical performance of point-of-care faecal immunochemical tests for haemoglobin. (May 2021) - O'Driscoll, Shane; Carroll, Magdalen; Maclean, William; Piggott, Carolyn; Jourdan, Iain; Benton, Sally C
Background: The faecal immunochemical test (FIT) detects the presence of haemoglobin (Hb) in faeces. It is used as a screening tool for colorectal cancer (CRC) and increasingly to triage patients presenting with symptoms of CRC. A number of quantitative point-of-care (POC) FIT systems marketed for professional use and intended for use in a clinical setting are available. Here we reviewed the POC FIT systems available; three (Eurolyser Cube, OC-Sensor iO and QuikRead go) were evaluated to assess their performance against manufacturers' claims and suitability for use in a clinical setting. Methods: The analytical evaluation of the POC FIT systems was undertaken using Hb lysates, patient samples and an external quality assessment sample. The evaluation focused on linearity, recovery, imprecision, prozone effect, Hb variant detection and suitability for use in a clinical setting. Results: All three POC FIT systems performed to their manufacturer's claims and demonstrated good analytical performance with acceptable linearity, recovery, within- and between-run imprecision. The QuikRead go and OC-Sensor iO were able to accurately detect samples with results above their measuring range. However, because of a prozone effect the Eurolyser Cube gave falsely low results when using high concentrations of Hb. The QuikRead go performed best in the usability assessment due to portability and timeliness of result. Conclusion: Each system performed according to their manufacturers' claims. The QuikRead go and OC-Sensor iO are suitable for use. The Eurolyser Cube is not recommended because of the risk of falsely low results.